Comparison of Respiratory Outcomes between Less Invasive Surfactant Administration and the Intubation-Surfactant-Extubation Technique in Premature Infants with Respiratory Distress Syndrome - Hye Seon Kim; Hyun Ho Kim; Misun Yang; Yea Seul Han; Se In Sung; So Yoon Ahn; Yun Sil Chang; Won Soon Park (Korean Society of Neonatology, 2020)
Purpose To compare respiratory outcomes between less invasive surfactant administration (LISA) and the intubation-surfactant-extubation (INSURE) technique in premature infants with respiratory distress syndrome (RDS). Methods We performed a retrospective medical chart review for 75 premature infants who were born at a gestational age (GA) of ≤34 weeks (between January 2017 and December 2019) and developed RDS after birth. Data on the demographic and outcome variables, including respiratory outcomes, were collected and compared between the infants who received LISA and those who received INSURE as a rescue therapy for RDS. Results No signifcant differences in GA, birth weight, and other demographic characteristics were found between the LISA and INSURE groups (GA: 28.7 weeks vs. 28.8 weeks, P=0.449; birth weight: 1,236 g vs. 1,124 g, P=0.714). At the delivery room, although the infants showed no significant difference in positive pressure ventilation rate after birth, the LISA group showed a higher rate of continuous positive airway pressure application than the INSURE group. The infants in the LISA group presented a higher risk of requiring multiple doses of surfactant for RDS than the infants in the INSURE group (57% vs. 17.5%, P=0.001). However, the duration of invasive and/or noninvasive respiratory support and incidence of bronchopulmonary dysplasia showed no signifciant difference between the two groups. Conclusion In the present study, no significant differences in the incidence of inhospital respiratory outcomes such as bronchopulmonary dysplasia were found between the LISA and INSURE groups. These results suggest that LISA can be an alternative therapeutic option for treating RDS to avoid intubation and mechanical ventilation in premature infants.